Enhanced catalytic performance of a Pt-xCeO2/Graphene catalyst for DMFCs by adjusting the crystal-plane and shape of nanoscale ceria1. Issue 91 (9th October 2015) - Wang, Weihua; Zhu, Mingda; Lu, Xiaolin; Gao, Yanfang; Li, Lijun; Cao, Zhenzhu; Li, Caihong; Liu, Jinrong; Zheng, Haitao
<x xml:space="preserve">Abstract</x> Oxygen storage capacity is influenced by the morphology and crystal-plane(s) of CeO2, which can thus affect the ability of this material to oxidise carbon monoxide.